2016
DOI: 10.1016/j.parepi.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

First report of Anatoecus dentatus in domestic duck ( Anas platyrhynchos domesticus , Linnaeus, 1978) from Southern India

Abstract: Parasitic infection is one of the prime causes for morbidity and mortality of ducks in India. Ducks have the habit of wading through the water resources especially paddy fields and feeding on snail which favours occurrence of various parasites. Among the parasites, lice infestation affects growth and productivity of ducks by way of irritation. Lice are well adapted as external parasites and usually are more a nuisance than a threat to their hosts. A nomadic farmer from Mannargudi area of Cauvery delta region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Goniocotes hologaster lice could be found in ducks with a prevalence of 100%, the study is conducted on a sample of 20 ducks (Musa et al, 2012). According to research conducted by Narayanaperumal et al, (2016) in South Indian region, predilection of Anatoecus dentatus lice is found on the edges of beak and head of ducks. Menopon gallinae lice most commonly found on the ventral side, namely 37.13% and Anaticola sp, most commonly found on wings, namely 59.09% (Fatimatussyahro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Goniocotes hologaster lice could be found in ducks with a prevalence of 100%, the study is conducted on a sample of 20 ducks (Musa et al, 2012). According to research conducted by Narayanaperumal et al, (2016) in South Indian region, predilection of Anatoecus dentatus lice is found on the edges of beak and head of ducks. Menopon gallinae lice most commonly found on the ventral side, namely 37.13% and Anaticola sp, most commonly found on wings, namely 59.09% (Fatimatussyahro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are 33.51 million of ducks as per 20th livestock census against 23.53 million in 19th livestock census that shows a change of 42.36% which means that there is an increase in demand of duck and duck farming which further warrants the need for proper surveillance and monitoring of diseases affecting ducks thereby controlling them. Small, marginal farmers and nomadic tribes practice duck farming in India which is sometimes seasonal ( Jeyathilakan et al, 2016 ). Ducks play an important role in rural livelihood as they cater to sustained meat and egg production.…”
Section: Introductionmentioning
confidence: 99%